Why bad feelings predict good behaviours: The role of positive and negative anticipated emotions on consumer ethical decision making. (30th July 2019) - Escadas, Marco; Jalali, Marjan S.; Farhangmehr, Minoo
Abstract: Research suggests that emotions can greatly influence consumer decision making and behaviours. Notwithstanding, our understanding of the role of anticipated emotions in what is an inherently complex deliberation process—that of consumer ethics—is still quite limited. The present study thus aims to address this gap, in two key ways: first, by measuring the influence of positive and negative anticipated emotions at each stage of the consumer ethical decision making process; and second by describing the specific emotions that most affect each component of the consumer ethical deliberation process and assessing their relative weight in predicting decisions involving ethical issues. Through the examination of 603 ethical situations and using multiple regression analysis, the findings indicate that anticipated emotions can account for up to 59% of the variance in consumer decisions involving ethics. Anticipating the experience of negative emotions as a result of carrying out an unethical behaviour was the affective component found to most influence consumer ethical deliberation process; and anticipated guilt was the discrete emotion exerting the greatest effect on consumer decision making in ethical situations. The findings indicate that more than feeling good, consumers avoid feeling bad; such that ethically favourable decisions emerge to prevent experiencing negative emotions in the future.